2012
DOI: 10.22358/jafs/66055/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pectin and rye on amino acid ileal digestibility, threonine metabolism, nitrogen retention, and morphology of the small intestine in young pigs

Abstract: The effects of supplementing cereal-based diets with 0, 40, or 80 g of pectin (P) or 270 g of rye (R) per kg on ileal digestibility of protein and amino acids (AA), and digesta viscosity in pigs of 20 kg body weight (BW), and on growth performance, nitrogen balance, small intestinal morphology, and threonine metabolism parameters in pigs of 15 kg BW were assessed. Digesta viscosity was increased more by 80 g than by 40 g P or by R. Ileal digestibility of AA and nitrogen retention were negatively affected by P,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…However, the possible effect on the mucus layer, which was also observed for the CP treatments, may suggest a higher susceptibility to bacterial translocation ( 44 ). Furthermore, both CP treatments reduced the acidic goblet cell counts in the small intestine indicating a lower mucus production, in line with Hedemann et al ( 45 ) and Swiech et al ( 46 ). Interestingly, no modification of the mucin 1 gene ( MUC1 ) was observed in this study, indicating the difficulty of data interpretation as not all parameters always go in the same line.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the possible effect on the mucus layer, which was also observed for the CP treatments, may suggest a higher susceptibility to bacterial translocation ( 44 ). Furthermore, both CP treatments reduced the acidic goblet cell counts in the small intestine indicating a lower mucus production, in line with Hedemann et al ( 45 ) and Swiech et al ( 46 ). Interestingly, no modification of the mucin 1 gene ( MUC1 ) was observed in this study, indicating the difficulty of data interpretation as not all parameters always go in the same line.…”
Section: Discussionsupporting
confidence: 86%
“…(44). Furthermore, both CP treatments reduced the acidic goblet cell counts in the small intestine indicating a lower mucus production, in line with Hedemann et al (45) and Swiech et al (46). Interestingly, no modification of the mucin 1 gene (MUC1)…”
Section: Discussionsupporting
confidence: 75%
“…However, this study failed to observe the positive effects of SBP on gut immunity and barrier function as well as diarrhea rate, which indicates its mode of action may not only be through the modulation of gut microbiota. Pectin, the main component of SBP, has been shown to increase digesta viscosity, but impair intestinal architecture and the mucus layer in young piglets, which may be a reason for the undesirable effects of SBP ( Hedemann et al., 2006 ; Święch et al., 2012 ). Unexpectedly, the alternation in microbial composition induced by SBP had no effects on the concentrations of SCFA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study [13] reported that a greater AID and a similar ATTD of CP was found for weaned pigs fed diet with 20% RDP than pigs fed control diet for a 42-d experiment. Moreover, piglets fed pectin-containing diet showed higher digesta viscosity with decrease ileal digestibility of protein [42]. Thus, and in the limit of variance indicators failure, the numerical decrease in AID and ATTD of CP in RDP diets could be related to high pectin content.…”
Section: Digestibilitymentioning
confidence: 94%